Subarachnoid Catheter Placement After Wet Tap for Analgesia in Labor: Influence on the Risk of Headache in Obstetric Patients. Issue 6 (1st November 2003) - Ayad, Sabry; Demian, Yousef; Narouze, Samer N; Tetzlaff, John E
Abstract : Background and Objectives: The incidence of postdural puncture headache (PDPH) after epidural wet tap for obstetric patients may be as high as 75%. We have studied how subsequent placement of a subarachnoid catheter immediately after confirmation of a wet tap, and leaving the catheter in place for 24 hours affects the incidence of PDPH. Methods: Over a 5-year interval, 115 consecutive patients who had unintentional dural puncture were divided into 3 groups by consecutive assignment. Group A had an epidural catheter placed at another interspace. Group B had a subarachnoid catheter placed for labor analgesia that was removed immediately after delivery. Group C had a subarachnoid catheter that was left in place for 24 hours after delivery. Data were collected retrospectively. The incidence of PDPH and blood patch was compared between groups. Results: The overall incidence of PDPH was 46.9% and need for blood patch 36.5%, significantly less in both subarachnoid catheter groups, 31% in B and 3% in group C, compared with group A (PDPH 81%) ( P < .001). Conclusion: Subarachnoid catheter placement after wet tap in obstetric patients reduces the PDPH rate and does so to a greater extent if left in place for 24 hours after delivery.